Effect of Ecological Elements in Pollution of Tehran and Management Role in Decreasing Pollution based on Synoptic Stations - Sabzevari, Azadeh Arbabi; Bayat, Mitra (International Journal of Bio-resource and Stress Management, 2014)
Air pollution is one of the most important effective parameters in urban micro-climatology and increasing population. Excessive use of fossil fuel resources, no use of environmentally friendly technologies and more importantly, the absence of proper environmental management are signs of growing urban climate change. Study on the influence of climatic factors like temperature, humidity, precipitation is important for climate change concerned. In this study, these aspects of Tehran's climate have been preliminary studied over the last two decades. The temperature has constantly increased, humidity and precipitation ha decreased. Dependant of the climatic factors are measured and analyzed. The green space of Tehran is not based on standard protocol and this make the weather of Tehran critical. The ecological impact of climatic elements is obvious to reduce the negative effects of these elements, need good management.